2022
DOI: 10.5267/j.ijdns.2022.5.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of online consumer reviews on purchasing intention through product mental image

Abstract: The aim of the study is to examine the impact of online consumer reviews on purchasing intention through product mental image. The primary sources represented by the instrument were distributed to the study population consisting of consumers of cosmetics in Jordan. Recently, the phenomenon of selling cosmetics through Internet websites and social media platforms has spread widely in Jordan. Therefore, Google Forms was used to design the research instrument and ask consumers of these products to respond to it b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…It can be understood as an integration between information and communication technologies (ICT) and manufacturing processes, therefore, ICT and technologies of manufacturing are regarded as two pillars of Industry 4.0 (Alshawabkeh et al, 2022;Tariq et al, 2022;Alolayyan et al, 2022;Dalenogare et al, 2018). A key theme of Industry 4.0 is a cyber-physical production system, which is based on knowledge integration to achieve agility in production systems (Sony & Naik, 2019).There are many technologies of Industry 4.0 such as Internet of Things (IoT), big data, artificial intelligence, additive manufacturing (Ertz et al, 2022;Khalayleh & Al-Hawary, 2022;AL-Zyadat et al, 2022), enterprise resource planning (ERP), social product development, radio frequency identification (RFID), and cloud-based manufacturing (Mohammad et al, 2022;Al-Abbadi et al, 2022;Sony & Naik, 2019). In terms of its benefits, prior works (e.g., Dalenogare et al, 2018) cited 14 expected benefits of Industry 4.0 including improving product customization, enhancing product quality, reducing operational costs, increasing productivity, and elevating process control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be understood as an integration between information and communication technologies (ICT) and manufacturing processes, therefore, ICT and technologies of manufacturing are regarded as two pillars of Industry 4.0 (Alshawabkeh et al, 2022;Tariq et al, 2022;Alolayyan et al, 2022;Dalenogare et al, 2018). A key theme of Industry 4.0 is a cyber-physical production system, which is based on knowledge integration to achieve agility in production systems (Sony & Naik, 2019).There are many technologies of Industry 4.0 such as Internet of Things (IoT), big data, artificial intelligence, additive manufacturing (Ertz et al, 2022;Khalayleh & Al-Hawary, 2022;AL-Zyadat et al, 2022), enterprise resource planning (ERP), social product development, radio frequency identification (RFID), and cloud-based manufacturing (Mohammad et al, 2022;Al-Abbadi et al, 2022;Sony & Naik, 2019). In terms of its benefits, prior works (e.g., Dalenogare et al, 2018) cited 14 expected benefits of Industry 4.0 including improving product customization, enhancing product quality, reducing operational costs, increasing productivity, and elevating process control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media is the means that generated the consumer, and represents a diverse source of information on the Internet, which is used by consumers to inform each other about the products, the brand, the services and the problems they face, as social media includes several types of information exchange on the Internet, and this includes networks Social media such as Facebook, MySpace, Friendster, and blogging sites such as Twitter) (Al-Nawafah et al, 2022;Al-Abbadi et al, 2022;Mohammad et al, 2022;Acar, 2019).The term "social media" refers to a collection of web-based programs built on the philosophical and technological underpinnings of Web 2.0 that enable the production and exchange of user-generated content, the exchange of content, and the capacity for interaction with other users and supporters of brands. ; makes it an ideal management in media marketing and consumer engagement as a tool for enabling decision-making and obtaining reliable information (Khalayleh & Al-Hawary, 2022;Altarifi et al, 2015;Koshy, 2013).…”
Section: Social Media Marketingmentioning
confidence: 99%
“…To better define the review quality, we synthesized the characteristics of these three attributes by using The Automated Readability Index (i.e. ARI) [31], as defined in (1).…”
Section: B1 Definition Of Review Qualitymentioning
confidence: 99%
“…Researchers reported that individuals' benefits as recipients gravitate around trust and usefulness gained from the reviews, regardless of the domain, for example sales [1] [18] or in the hospitality and tourism industry [37] [38], just to name a few. According to data from a survey, 77% of consumers read online reviews, and 75% trust online reviews more than personal recommendations [25].…”
Section: Introductionmentioning
confidence: 99%